Seasonal variation of bacterial endophytes in urban trees - Shen, Shu Yi; Fulthorpe, Roberta (Frontiers in Microbiology, 2015)
Bacterial endophytes, non-pathogenic bacteria residing within plants, contribute to the growth and development of plants and their ability to adapt to adverse conditions. In order to fully exploit the capabilities of these bacteria, it is necessary to understand the extent to which endophytic communities vary between species and over time. The endophytes of Acer negundo, Ulmus pumila and Ulmus parvifolia were sampled over three seasons and analyzed using culture dependent and independent methods (culture on two media, terminal restriction fragment length polymorphism, and tagged pyrosequencing of 16S ribosomal amplicons). The majority of culturable endophytes isolated were Actinobacteria, and all the samples harbored Bacillus, Curtobacterium, Frigoribacterium, Methylobacterium, Paenibacilllus and Sphingomonas species. Regardless of culture medium used, only the culturable communities obtained in the winter for A. negundo could be distinguished from those of Ulmus spp.. In contrast, the nonculturable communities were dominated by Proteobacteria and Actinobacteria, particularly Erwinia, Ralstonia and Sanguibacter spp.. The presence and abundance of various bacterial classes and phyla changed with the changing seasons. Multivariate analysis on the culture independent data revealed significant community differences between the endophytic communities of A. negundo and Ulmus spp., but overall season was the main determinant of endophytic community structure. This study suggests investigations of the studies ofendophytic populations of urban trees should expect to find significant seasonal and species-specific community differences and sampling should proceed accordingly.